2016
DOI: 10.1073/pnas.1613833113
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of natural variation in visual senescence in Drosophila

Abstract: Senescence, i.e., functional decline with age, is a major determinant of health span in a rapidly aging population, but the genetic basis of interindividual variation in senescence remains largely unknown. Visual decline and age-related eye disorders are common manifestations of senescence, but disentangling age-dependent visual decline in human populations is challenging due to inability to control genetic background and variation in histories of environmental exposures. We assessed the genetic basis of natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 101 publications
1
60
0
Order By: Relevance
“…This is expected, since sexual dimorphism is a common feature of the genetic architecture of complex traits and has been documented for every trait analyzed to date in the DGRP, including but not limited to alcohol sensitivity (Morozova et al , 2015), sleep phenotypes (Harbison et al , 2013), olfactory behavior (Swarup et al , 2013), feeding behavior (Garlapow et al , 2015), and visual senescence (Carbone et al , 2016). …”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This is expected, since sexual dimorphism is a common feature of the genetic architecture of complex traits and has been documented for every trait analyzed to date in the DGRP, including but not limited to alcohol sensitivity (Morozova et al , 2015), sleep phenotypes (Harbison et al , 2013), olfactory behavior (Swarup et al , 2013), feeding behavior (Garlapow et al , 2015), and visual senescence (Carbone et al , 2016). …”
Section: Discussionmentioning
confidence: 93%
“…It should be noted, however, that the AIP is derived from only 37 DGRP lines and contains 66% of the allelic variants present in the DGRP. Previous studies showed that despite differences in network compositions derived from GWA analyses in the DGRP and extreme QTL mapping in AIPs the genetic networks relate to the same cellular processes (Carbone et al , 2016, Morozova et al , 2015, Shorter et al , 2015, Swarup et al , 2013). We note that gene interactions and network architecture can vary based on developmental stage, tissue, and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine the relationship between variation in gene expression and variation in organismal quantitative trait phenotypes, we chose 11 quantitative traits with published phenotypic data (chill coma recovery time and startle response 19 ; starvation resistance 20 ; day and night sleep bout number, day and night total sleep duration, and total waking activity 35 ; food consumption 36 ; male aggression 37 ; phototaxis 38 ); and additionally measured five metabolic traits (levels of free glucose, glycogen, free glycerol, triglyceride and protein) and three metrics of body size (body weight, thorax length, thorax width). All traits were quantified in the same laboratory under the same culture conditions used in this study.…”
Section: Resultsmentioning
confidence: 99%